An offline technique to evaluate residual motion of the diaphragm during deep inspiratory breath-hold from cone-beam CT datasets - Blessing, Manuel; Vogel, Lena; Boda-Heggemann, Judit; Wenz, Frederik; Stieler, Florian; Simeonova-Chergou, Anna (Strahlentherapie und Onkologie, 2018)
PurposeIn radiation therapy, the computer-assisted deep inspiration breath-hold (DIBH) technique is one approach to deal with respiratory motion of tumors in the lung, liver, or upper abdomen. However, inter- and intra-breath-hold deviations from an optimal static tumor position might occur. A novel method is presented to noninvasively measure the diaphragm position and thus estimate its residual deviation (as surrogate for the tumor position) based on cone-beam computed tomography (CBCT) projection data using active breathing control during acquisition.MethodsThe diaphragm dome (DD) position relative to the isocenter of a linear accelerator is known from the static (DIBH) planning CT. A ball-bearing phantom (BB) is placed at this position, a CBCT dataset is acquired, and in each projection the position of the projected BB is determined automatically based on thresholding. The position of the DD is determined manually in CBCT projections of a patient. The distance between DD and BB (ideal static setting) in craniocaudal direction is calculated for a given angle based on the distance in the projection plane and the relative position of the BB referring to the source and the detector. An angle-dependent correction factor is introduced which takes this geometrical setting into account. The accuracy of the method is assessed.ResultsThe method allows a CBCT projection-based estimation of the deviation between the DD and its optimal position as defined in the planning CT, i.e., the residual motion of the DD can be assessed. The error of this estimation is 2.2 mm in craniocaudal direction.ConclusionsThe developed method allows an offline estimation of the inspiration depth (inter- and intra-breath-hold) over time. It will be useful as a reference for comparison to other methods of residual motion estimation, e.g., surface scanning.
Gesehen am 16.10.2019